TOTAL BAKTERI DAN SIFAT ORGANOLEPTIK MINUMAN SARI TEMPE DENGAN VARIASI WAKTU PENYIMPANAN - Kusmanto -; Ana M. Hidayati (Jurnal Pangan dan Gizi, 2011)
Juice tempeh (Misape) processed from raw materials soybean tempeh.unhygienic processing will lead to the emergence of bacteria that are pathogenic contaminants so that the need for supervision to ensure food safety . The purpose of the study was to analyze the total bacterial and organoleptic properties Misape with duration of storage of 0 , 3 , 6 , 9 , and 12 days at a temperature of 5-8o C with 5 replicates , were tested in duplicate analysis. Obtained from the study showed that the total bacterial misape row is 1.1 x 101 , 1.7 x 101 , 4.1 x 101 , 3.4 x 101 , 3.6 x 101 . Total bacteria increased from day storage 0 to 6 , then on day 9 began to decline . ANOVA test results it is concluded no effect of storage time on the total bacteria in misape . Based on organoleptic test panelists could still receive the color , aroma , consistency and flavor during storage misape 0 , 3 , 6 , 9 and 12 days . Friedman Test results on organoleptic properties showed no effect of duration of storage on the flavour, viscosity and taste misape .